1993
DOI: 10.1136/bmj.306.6876.481
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of severe acute renal failure in adults: results of a community based study.

Abstract: Objective-To determine the age related incidence of severe acute renal failure in adults in two

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
116
1
13

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(138 citation statements)
references
References 11 publications
8
116
1
13
Order By: Relevance
“…Advanced resuscitation techniques may have shifted the spectrum of acute renal failure towards patients who would not previously have survived. One group has demonstrated that despite the increased burden of chronic illness, the outcome for renal failure in the ICU has improved [14]; however, the improved survival was limited to patients with APACHE II scores of less than 21 and no improvement was seen in the most severely ill. As in previous studies, we found that nonsurviving patients were significantly older [15±17] but not all authors agree that age has a negative influence on survival [11,12].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Advanced resuscitation techniques may have shifted the spectrum of acute renal failure towards patients who would not previously have survived. One group has demonstrated that despite the increased burden of chronic illness, the outcome for renal failure in the ICU has improved [14]; however, the improved survival was limited to patients with APACHE II scores of less than 21 and no improvement was seen in the most severely ill. As in previous studies, we found that nonsurviving patients were significantly older [15±17] but not all authors agree that age has a negative influence on survival [11,12].…”
Section: Discussionsupporting
confidence: 71%
“…In that study renal failure was defined as a creatinine of greater than 177 mmol.l 21 or a sudden rise in serum creatinine of more than 50% from baseline in mild to moderate chronic renal failure. A UK study based on laboratory data, and using a creatinine of greater than 500 mmol.l 21 to define severe acute renal failure, found an incidence of 140.5 per million of the total population [12]. We have found an incidence of combined renal and respiratory failure in adult general intensive care units of 55 per million of the population per annum.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Data in the literature are ambiguous on this point. Two community-based studies found that older age was associated with a higher incidence of ARF (11,40). In a general medical ICU population and in a population of patients undergoing myocardial revascularization, age was an independent factor associated with the development of ARF in multivariable analysis (14,24,35).…”
Section: Discussionmentioning
confidence: 96%
“…1 In patients .60 years of age, there is a 3-to 8-fold progressive and age-dependent increase in the frequency of AKI. [2][3][4] The elderly also suffer increased rates of progression to CKD, ESRD, and death after an episode of AKI compared with younger patients. 5 Because the number of United States citizens ages 65 years old or older will double over the next 20 years, the burden of AKI in this group will be substantial.…”
mentioning
confidence: 99%